x y z + 1 3 x + 1 3 y + 1 3 z = 0
x y z + 1 3 x − 1 3 y + 1 3 z = 0
x y z + 1 3 x − 1 3 y − 1 3 z = 0
x y z − 1 3 x − 1 3 y − 1 3 z = 0
x y z − 1 3 x + 1 3 y − 1 3 z = 0
x y z − 1 3 x + 1 3 y + 1 3 z = 0
y = 0
x = − z
Solve for x , y , z
Enter either − 1 for no solution or 1 for a solution
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If y=0, xyz would've equal 0 and not necessarily equal xz
If x y z and y = 0 , usually the accepted answer for the whole equation will be 0, thereby the whole expression x y z will be eliminated
Great solution though
Most solved problem in my profile! 2 6 and upwards... @Hamza Anushath
Only from the last three equations: x = y = z = 0
Nice! Wait for my solution, I guess? I was typing it...
Log in to reply
Okay! Are we going another round in the evening? With more time...
Log in to reply
Sure! Why not...
I just forgot, you need to do it in the Out of Hours Comment Room
The time is out of hours...
What do you think of my solution, @Páll Márton ?
Log in to reply
Your solution is very long, but correct. My way: y = 0 ; x = − z , therefore the last x y z equation: 0 − 1 3 x + 0 − 1 3 x = 0 . So x = y = z = 0 . This means that we can eliminate the variables: 0 ± 0 ± 0 ± 0 = 0 .
Log in to reply
Nice, but you need to prove that for all equations. Hence why my solution is very long.
Log in to reply
@A Former Brilliant Member – Ok! Now go to solve the daily problem. 1 minute...
Log in to reply
@A Former Brilliant Member – And my problem was bad, so I have deleted that and uploaded a new.
Log in to reply
@A Former Brilliant Member – C - answer was A...
x =y=z=0 and a suggestion brilliant gives you three chances and there are only two possibility :-P lol
As y = 0 , we can eliminate some expressions from the list of equations
1 3 x + 1 3 z
1 3 x − 1 3 z
1 3 z − 1 3 x
− 1 3 z − 1 3 x
Replacing x with − z
1 3 x − 1 3 x
1 3 x + 1 3 x
− 1 3 x − 1 3 x
1 3 x − 1 3 x
The double of a number will never be equal to zero unless the number itself is zero
As x is zero, we have also proved that z = 0 , as x = − z
@Yajat Shamji , looks like I made your question too easy, with mathematical working applied. Tell me if there is any flaw in my working, okay?
Log in to reply
You mean z with − x , no? @Hamza Anushath
Log in to reply
What are you trying to say?
Log in to reply
Your title says "A possible problem...?" The link says "An impossible problem"
Log in to reply
@A Former Brilliant Member – Oh. I renamed it after the link was made.
Problem Loading...
Note Loading...
Set Loading...
Since y = 0 , we can eliminate the y variable:
x z + 1 3 x + 1 3 z = 0
x z + 1 3 x + 1 3 z = 0
x z + 1 3 x − 1 3 z = 0
x z − 1 3 x − 1 3 z = 0
x z − 1 3 x − 1 3 z = 0
x z − 1 3 x + 1 3 z = 0
Now, since all 6 equations are the same, we can eliminate 3 of them to create 3 simultaneous equations:
x z − 1 3 x − 1 3 z = 0
x z − 1 3 x + 1 3 z = 0
x z + 1 3 x − 1 3 z = 0
Now, since x = − z , this must mean that z = − x . We will now take two routes:
Route 1 - x = − z :
Substitute x = − z into the simultaneous equations:
− z ( z ) − 1 3 ( − z ) − 1 3 z = 0
− z ( z ) − 1 3 ( − z ) + 1 3 z = 0
− z ( z ) + 1 3 ( − z ) − 1 3 z = 0
Simplify:
− z + 1 3 z − 1 3 z = 0
− z + 1 3 z + 1 3 z = 0
− z − 1 3 z − 1 3 z = 0
Simplify even further:
− z = 0
− z + 2 6 z = 0
− z − 2 6 z = 0
Simplify the second equation even further:
2 5 z = 0 , z = 0
Simplify the third equation even further:
− 2 7 z = 0 , z = 0
Since x = − z , x = 0
Route 2 - z = − x :
Substitute z = − x into the simultaneous equations:
x ( − x ) − 1 3 x − 1 3 ( − x ) = 0
x ( − x ) − 1 3 x + 1 3 ( − x ) = 0
x ( − x ) + 1 3 x − 1 3 ( − x ) = 0
Simplify:
− x − 1 3 x + 1 3 x = 0
− x − 1 3 x − 1 3 x = 0
− x + 1 3 x + 1 3 x = 0
Simplify even further:
− x + 2 6 x = 0
− x − 2 6 x = 0
− x = 0
Simplify the second equation even further:
2 5 x = 0 , x = 0
Simplify the third equation even further:
− 2 7 x = 0 , x = 0
Since z = − x , z = 0
In both routes x = z = 0 . Now since y = 0 , x = y = z = 0 . We have a solution!
Therefore, the answer is 1 .